1982
DOI: 10.1002/chin.198233135
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS OF AROMATIC HYDROCARBONS FROM 1,2,3‐SELENADIAZOLES AND α‐PYRONES

Abstract: Die Selenadiazole (I), (IV), (VI), (VIII), (X) und (XII) spalten beim Erhitzen Se und N2 ab unter Bildung der entsprechenden Cycloalkine, die in situ mit α‐Pyron (II) zu den literaturbekannten Aromaten (III), (V), (VII), (IX).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Controllable, site-specific reactions are highly valuable for multiplexing of (bio)molecules and expansion of labeling diversity. Early studies during the 1970s and 1980s described the reaction of plain cyclooctyne with various 1,2-quinones in organic solvents. It has also been shown that 1,2-quinones can be generated on proteins by selective periodate oxidation of genetically incorporated 3,4-dihydroxy- l -phenylalanine ( l -DOPA), leading to slow (5 h) conjugation with a polysaccharide . We aimed to explore the facile catechol-to-quinone conversion as a fast, chemically activatable bioconjugation by strain-promoted chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Controllable, site-specific reactions are highly valuable for multiplexing of (bio)molecules and expansion of labeling diversity. Early studies during the 1970s and 1980s described the reaction of plain cyclooctyne with various 1,2-quinones in organic solvents. It has also been shown that 1,2-quinones can be generated on proteins by selective periodate oxidation of genetically incorporated 3,4-dihydroxy- l -phenylalanine ( l -DOPA), leading to slow (5 h) conjugation with a polysaccharide . We aimed to explore the facile catechol-to-quinone conversion as a fast, chemically activatable bioconjugation by strain-promoted chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Another [4 + 2] IEEDA cycloaddition reaction is the reaction between an ortho -quinone (e.g. 31 ) and a cyclooctyne ( 32 ) under formation of diketone 33 (Figure A) or between ortho -quinone 34 and olefin 35a /alkyne 35b to form bicyclo[2.2.2]­octadiene diketone 36a or 36b (Figure B). , Applications of this reaction in more complex settings will be treated below; here we focus on the model studies that were used in order to determine the rates, scope, and limitations of this conversion. Specifically, the model substrate 4- tert -butyl-1,2-benzoquinone 34 was used to determine the reaction rate constants with various strained alkenes and alkynes (Figure C).…”
Section: Small Moleculesmentioning
confidence: 99%
“…5 Tribenzo[ a , c , f ]cyclooctanes are primarily synthesized by Diels–Alder reaction of strained acetylenes with cyclic dienes including α-pyrones (Fig. 1, a) 6 and furan (Fig. 1, b) 7 followed by subsequent deoxygenation.…”
mentioning
confidence: 99%